In-Silico Study to Design Foot and Mouth Disease Vaccine Candidates - Andayani, I Gusti Ayu Sri; Depamede, Sulaiman Ngongu; Dradjat, Adji Santoso; Sriasih, Made (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Foot and Mouth Disease (FMD) is a viral disease that affects livestock and can cause significant economic losses. Vaccination has been recognized as the primary strategy for FMD prevention, but vaccine development, especially conventional vaccine production, has time, cost, and effectiveness limitations. Using software-based immunoinformatics methods has cost and time efficiency for simulation development and calculations in vaccine development research. This study aimed to design FMD vaccine candidates using an epitope-based in-silico approach, focusing on identifying potential epitopes of the pathogen that causes FMD. The in silico approach was used to analyze FMD virus genome sequences from UniProtKB (https://www.ebi.ac.uk/Tools/msa/clustalo) and the National Library of Medicine application (https://www.ncbi.nlm.nih.gov). Furthermore, the prediction of FMD virus epitopes was analyzed using the Immuno-Epitope database, and the prediction of peptide antigenicity levels using VaxiJen 2.0 software. The analysis identified eight potential epitope candidates, such as CSIQKR, TEFGFHPNA, EIRPMEKVRA, YEGVEL, SFARRGT, APGLPWALQGKRRGALIDFESGTV, MASLEDKGKPF, and TLPTSFNYGAI with antigen binding affinities of 2. 9424nM, 1.65nM, 1.4702nM, 1.2966nM, 1.2643nM, 1.1967nM, 1.1921nM and 1.0143nm respectively. These epitopes are expected to form the basis for developing more selective and safe peptide vaccines. By focusing on epitopes, the resulting vaccine can improve the effectiveness and safety of vaccination and accelerate the development of new vaccines for FMD prevention.